In vitro CYTOTOXIC POTENTIAL OF TURBINARIA CONOIDES AND SARGASSUM PLAGIOPHYLLUM EXTRACT UPON BJ CELL LINE - VENNILA, K. KANMANI; HILDA, K.; JANARTHANAN, S.; MARTIN, P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Marine algae produce complex polysaccharides and sterols, which has spectacular therapeutic values. These biologically active molecules rich in carbon sources were denoted as secondary metabolites, which were known for their biological activity as anti-coagulant, anti- inflammatory, anti-bacterial, anti-tumor and cytotoxic effect upon certain cell lines. Marine brown algae Turbinaria belongs to the family Sargassaceae were inedible, which possess oxygenated sterols shows cytotoxic properties. The extracts of brown algae from Turbinaria conoides and Sargassum plagiophyllum revealed the cell viability upon BJ cells with different concentrations. T. conoides hexane extract showed, non-toxicity for all the range from 3.5 to 500 µg/ml, unlike the other solvent extract of ethyl acetate and methanol upon the BJ cells. Present investigation intends to find the IC50 value of cytotoxic activity against BJ cell line (Human foreskin fibroblast cells) with three different solvent extracts (Hexane, Methanol, Ethyl acetate).